The Tropics Bite Back : Culinary Coups in Caribbean Literature - Loichot, Valerie, 1968- (Book collections on Project MUSE., 2013)
The ubiquitous presence of food and hunger in Caribbean writing - from folktales, fiction, and poetry to political and historical treatises - signals the traumas that have marked the Caribbean from the Middle Passage to the twenty-first century. This book traces the evolution of the Caribbean response to the colonial gaze (or, rather, the colonial mouth) from the late nineteenth century to the twenty-first. Unlike previous scholars, the author does not read food simply as a cultural trope. Instead, she is interested in literary cannibalism, which she interprets in parallel with theories of relation and creolization.